Comparison of Okun’s law test results for Croatia and Slovakia - Tomić, Daniel; Stjepanović, Saša; Grbac, Vanja (Oeconomica Jadertina, 2020)
With the publication of the work “Potential GNP: its measurement and significance” (Okun, 1962), the concept of Okun’s law became an important part of global macroeconomic issues. The empirically determined connection between the national product and unemployment, which is manifested through Okun’s law, belongs to a fundamental part of economic empiricism. Gross domestic product and unemployment are among the main macroeconomic variables that reflect the movement of a country’s economy. The countries we observe in this paper went through a transition period in the 1990s, namely a period of great economic, institutional and economic changes. Precisely because of these changes, we are interested in comparing the Slovak and Croatian economies and testing Okun’s law. The aim of this paper is to show whether Okun’s law is valid for Croatia and Slovakia, or whether there is a correlation between the observed variables for these countries. The final purpose of the paper is to show whether there are similarities between the two observed economies when it comes to Okun’s law. We will show this similarity based on the analysis of data for the period from 2000 to 2018 using vector autoregression. The results of the research have been presented at the end of the paper and they are related to the implications of economic policy in the sphere of the labour market that directly affect economic growth and development.
Keywords: Okun’s law; VAR model; economic implications; Slovakia; Croatia